The Rationalization of Movement in German Industry/Trade Associations and Industrial Control (Book). - Weidenhammer, Robert (The Accounting Review, 1934)
Reviews the books "The Rationalization of Movement in German Industry," by Robert A. Brady and "Trade Associations and Industrial Control," by Simon N. Whitney.